Primary Healthcare Services and Health-Related Quality of Life of Older Persons with Non-Communicable Diseases: A Narrative Literature Review - Fiona, Atim; Kiyinji, Frank; Orach-Meza, Faustino; Clarke Nanyonga, Rose (International Journal of Global Health, 2024)
In response to the rising burden of non-communicable disease (NDC), the World Health Organization (WHO) developed tools to enable early detection and management of NCDs in Primary Healthcare centers (PHC). Globally, the prevalence of NCDs remains alarmingly high with 41 million deaths annually. Of these, 17 million people die before the age of 70, and 86% of these premature deaths occur in low-and middle-income countries. This narrative review aimed to assess the effect of PHC services on health-related quality of life (HRQoL) of older persons with NCDs, to critically analyze the potential of the existing literature in informing improvements in PHC services. We searched various databases (PubMed, Springer, Scopus, and ScienceDirect) for relevant literature. Peer-reviewed articles on the influence of PHC services on HRQoL among older persons with NCDs written and published in English between January 2013 and May 2024 were considered. The review indicates that effective PHC services are linked to good HRQoL. However, PHC services are sub-optimal and poor in low- and middle-income countries, hence more health interventions are essential to improve PHC services to enhance HRQoL of older persons.
Keywords: Primary Healthcare Services; Health-related Quality of Life; Older Persons